Commercial Policy in Post-War Europe: Reciprocity Versus Most-Favored-Nation Treatment - Fay, H. Van V. (Quarterly Journal of Economics, 1927)
I. The situation before the war: The Cobden treaty and the general-conventional system, 443. — The double-schedule system, 444. — Opposition to the most-favored-nation clause, 445. — II. Principles under discussion after the peace, 446. — The right of access to raw materials, 447. — Freedom of transit, 448. — Equality of trade conditions, 449. — The treaty provisions and their effects, 450. — III. France's espousal of reciprocity, 456. — Influence on policies of other countries, 457. — Genoa conference of 1922, 458. — IV. Movements for a multilateral arrangement, 462. — Brussels conference of 1920, 462. — Barcelona conference of 1921, 463. — V. Development of most-favored-nation agreements in negotiations between individual states, 466. — The International Economic Conference of 1927, 469.